Chronic illness and long-term care breakthroughs in research and practice (IGI Global, 2019)
"This book features current research on the diagnosis, monitoring, management, and treatment of recurring diseases such as diabetes, Parkinson's disease, autoimmune disorders, and others. Highlighting a range of pertinent topics such as medication management, quality of life issues, and sustainable health"--Provided by publisher.